Assessment of the influence of daily shadings pattern on human thermal comfort and attendance in Rome during summer period. (October 2015) - Martinelli, Letizia; Lin, Tzu-Ping; Matzarakis, Andreas
Abstract: Solar access has a critical influence on human thermal comfort. In shaded areas, direct shortwave radiation fluxes decrease and a cooling effect is produced. The percentage and position of shaded areas in an open space depend on sun position and urban morphology, so they change during the day, affecting attendance distribution over time. The study assessed the relationship between daily shading patterns, attendance and thermal comfort during summer at San Silvestro square in Rome, Italy. Field investigations were conducted on 1 st and 2 nd August 2014, including meteorological measurements and unobtrusive observations. The assessment of thermal comfort was based on the Physiologically Equivalent Temperature (PET), calculated using the RayMan model. The majority of visitors at San Silvestro square sought shaded locations when sitting, resulting in a variation of attendance throughout the day. The attendance in unshaded location passed from 0 to 2 people at 11:00 to 2–10 at 12:00, whereas the attendance in shaded locations had a minimum of 0–4 at 12:00 and a maximum of 52–94 at 18:00. This preference was strongly correlated with thermal comfort analysis, as PET values were significantly lower in shaded areas. The minimum difference in the median of PET from shaded and unshaded locations was 2 °C at 18:00 and the maximum difference was 7 °C at 11:00. The main findings of this study highlight the importance of considering daily shading pattern when renovating open spaces in Mediterranean climate and can be used as reference for future renovations. Highlights: The study performs a field investigation in a square in Rome, Italy, during summer. It focuses on daily shading patterns, attendance and thermal comfort. Most of the visitors sought shaded locations when sitting. This preference was strongly correlated with thermal comfort analysis. PET index values were significantly lower in shaded areas.